IMPLEMENTASI HADIS RIWAYAT ABU DAWUD NO INDEKS 3891 OLEH JAM’IYYAH RUQYAH ASWAJA SIDOARJO - Umi Nashiroh Roihana Purnamasari; Muhid Muhid; Andris Nurita (IAIN Syekh Nurjati Cirebon, 2022)
Hadith is the second life guide after the Qur'an for Muslims, so it is important tounderstand the meaning of hadith applied in everyday life. Ruqyah is a treatment in the style of the Prophet, which is still in great demand today. With the development of the times, ruqyah treatment is also growing in society. This can be seen from the large number of social media and television featuring ruqyah treatment. In addition, now many organizations or groups are engaged in this medical field, so many ruqyah methods have emerged. But not all ruqyah practices are justified in Islam. The permissible implementation of ruqyah is one that uses verses from the Qur’an, prayers taught by the Prophet SAW, dhikr, and sholawat. Therefore, the formulation of the research problem is as follows: 1.) How is the understanding of the hadith narrated by Abu Dawud index no. 3891 by Jam'iyyah Ruqyah Aswaja Sidoarjo, 2.) How is the implementation of the hadith narrated by Abu Dawud index no. 3891 by Jam'iyyah Ruqyah Aswaja Sidoarjo. This writing is a qualitative field writing. The sources for this writing are practitioners at Jam'iyyah Ruqyah Aswaja Sidoarjo and special guidebooks for practitioners belonging to Jam'iyyah Ruqyah Aswaja. Data collection techniques were carried out using the interview method with practitioners at Jam'iyyah Ruqyah Aswaja Sidoarjo. The observation method when carrying out ruqyah, both ruqyah in bulk and individually. The documentation method is in the form of supporting files. Data analysis uses data in the field, where the data obtained is in the form of conclusions or verification results from interviews and observations of actual conditions. The result of this writing is the understanding of the hadith history of Sunan Abu Dawud no 3891 by Jam'iyyah Ruqyah Aswaja Sidoarjo. This hadith is a hadith that allows ruqyah by praying to Allah. The prayers contained in the hadith are also practiced in the ruqyah process by Jam'iyyah Ruqyah Aswaja Sidoarjo.